Plate 13: Papaver rhoeas - Fitton, Sarah Mary; Fitton, Elizabeth (Conversations on Botany, 1817)
Hand-colored lithograph of the common red poppy, Papaver rhoeas. Class Polyandria, order Monogynia.
Keywords: Poppies; Botany; Papaveraceae; Women botanists; Scientific illustration